2013
DOI: 10.1371/journal.pone.0078729
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Molecular Phenotypes in Male and Female Schizophrenia Patients

Abstract: BackgroundIn schizophrenia, sex specific dimorphisms related to age of onset, course of illness and response to antipsychotic treatment may be mirrored by sex-related differences in the underlying molecular pathways.Methodology/Principal FindingsHere, we have carried out multiplex immunoassay profiling of sera from 4 independent cohorts of first episode antipsychotic naive schizophrenia patients (n = 133) and controls (n = 133) to identify such sex-specific illness processes in the periphery. The concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 33 publications
5
49
1
Order By: Relevance
“…We found that prolactin is inversely related (0.83) with BD in males which is the opposite effect we found in a schizophrenia study (Ramsey et al, 2013). Further study of the gender effect of PRL on BD.…”
Section: Discussioncontrasting
confidence: 85%
“…We found that prolactin is inversely related (0.83) with BD in males which is the opposite effect we found in a schizophrenia study (Ramsey et al, 2013). Further study of the gender effect of PRL on BD.…”
Section: Discussioncontrasting
confidence: 85%
“…Because numerous studies have shown that the onset of schizophrenia tends to be later in life in women than in men (Howard et al, 2000), and the present results indicate that the separation between women with schizophrenia and HC women might differ from that between men with schizophrenia and HC men at various ages, understanding the effects of aging in schizophrenia will likely require studying LTL (and other aging parameters) separately in men and women (Ramsey et al, 2013).…”
Section: Discussionmentioning
confidence: 74%
“…These factors may be increased in schizophrenia compared to HCs (Emiliani et al, 2014;Muller et al, 2015;Shivakumar et al, 2014). This could, in theory, result in shortened LTL, but there is only mixed evidence that these factors are differentially prevalent in men vs women with schizophrenia (Joseph et al, 2015;Kunz et al, 2011;Lee et al, 2016;Ramsey et al, 2013;Reyazuddin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to psychiatric disorders, alterations in MDC levels have been found in patients suffering from schizophrenia [27,28] . Ramsey et al [27] compared untreated schizophrenic patients with healthy subjects and found sex-specific differences in the serum MDC levels of patients compared to in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Ramsey et al [27] compared untreated schizophrenic patients with healthy subjects and found sex-specific differences in the serum MDC levels of patients compared to in controls. No such differences could be found for patients suffering from MDD or bipolar disorder (BP).…”
Section: Discussionmentioning
confidence: 99%